KARAKTERISTIK STOMATA BERDASARKAN ESTIMASI WAKTU DAN PERBEDAAN INTENSITAS CAHAYA PADA DAUN Hibiscus tiliaceus Linn. DI PANGANDARAN, JAWA BARAT - Tia Setiawati; Inneke Febrihardianti Syamsi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Hibiscus tiliaceus L. is useful as shade plants, medicinal, and wood carvings. Optimizing utilization of plants depends on environmental conditions, one of which is sunlight that affects stomatal. Each plant has a different response to the stress of sunlight such as the ability to open and close the stomatal. This study aims to determine the differences in the stomatal characteristics of Hibiscus tiliaceus’s leaves based on time estimation and difference of light intensity were determined using the replica method in Pananjung Pangandaran Nature Reserve, West Java. The results showed that the lowest and highest average length and width of porous stomatal, the number of open and closed stomatal, and the density of stomatal in shaded areas were 6 µm (morning and noon), 2.77 µm (afternoon), 6, respectively. 93 µm (morning), 3.83 µm (afternoon), 43 cells, 8 cells, and 259.86 cells / mm2, whereas in the non-shaded area 5.5 µm (morning), 2.97 µm (afternoon ), 7 µm (day and evening), 4.1 µm (afternoon), 18 cells, 26 cells, and 224.20 cells / mm2. The opening of stomatal in the non-shaded area is greater than the shaded. The estimated time, difference light intensity, and physical factors influence the parameters of the study. Keywords: Hibiscus tiliaceus L., light intensity, stomatal characteristics, time estimation.